1996
DOI: 10.1136/gut.39.5.722
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three faecal occult blood tests in the detection of colorectal neoplasia.

Abstract: Methods and Aims-For the detection of colorectal neoplasia, 192 consecutive patients had colonoscopy to evaluate the sensitivity and specificity of three faecal occult blood tests (FOBT (Gut 1996; 39: 722-725) Australia Ltd) uses a monoclonal antibody that is specific for human haemoglobin, which theoretically should decrease the number of false positive test results. The BM Test colon albumin (BMCA) (Boehringer Mannheim, UK) is designed to detect human albumin present in the faecal sample, which may be as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…The studies that evaluated the standard guaiac-based FOBT that did not correct for verification bias are listed in Table 1. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] In the last study, the data was presented in two separate publications. These 19 studies included 713 subjects with colorectal cancer and 4181 controls.…”
Section: Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies that evaluated the standard guaiac-based FOBT that did not correct for verification bias are listed in Table 1. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] In the last study, the data was presented in two separate publications. These 19 studies included 713 subjects with colorectal cancer and 4181 controls.…”
Section: Included Studiesmentioning
confidence: 99%
“…Both control-and cancersubjects underwent a confirmatory test, usually a colonoscopy though some of the older studies also utilized barium enema and sigmoidoscopy, particularly if FOBT negative. Most studies included subjects who submitted 3 stool specimens [31][32][33][34]36,37,39,41,44,[46][47][48][49][50] while some studies included subjects who only submitted one specimen 35,42,43 or the number was not specified. 38,40,45 Almost all of the studies reported that the specimens were collected at home while one study did not specify the location.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] There are many reviews comparing the IFOBT to the formerly methods. [4], [5], [17] decide the most suitable cut-off value universally by discussing the efficiency and the probability to detect cancer. [25] The most suitable cut off value have to be decided never to fail to pick up a colorectal cancer and to reduce the false positive rate as low as possible.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of the monoclonal antibody method was superior to both Hemoccult ® II and BMTest colon albumin. Hope et al 17 concluded that the monoclonal antibody method, an FOBT that uses a monoclonal antibody specific to human hemoglobin, is a more accurate test in the detection of colorectal neoplasia and should be used in colorectal cancer screening programs. Unfortunately, as Yu and colleagues report, 9 only half of all colorectal cancers detected produce blood in the stool, with the remaining cancers producing false-negative results with the use of FOBT alone.…”
mentioning
confidence: 98%